Advances in Cysteine Protease B Inhibitors for Leishmaniasis Treatment - Rodriguez Gini, Ana Luísa [UNESP]; João, Emílio Emílio [UNESP]; Lopes, Juliana Romano [UNESP]; Da Cunha, Pamela Souza Tada [UNESP]; Arenas Velásquez, Angela Maria [UNESP]; Graminha, Marcia Aparecida Silva [UNESP]; dos Santos, Jean Leandro [UNESP]; Scarim, Cauê Benito [UNESP] (Bentham Science Publishers, 2025)
The expression and release of cysteine proteases by Leishmania spp. and their virulence factors significantly influence the modulation of host immune responses and metabolism, rendering cysteine proteases intriguing targets for drug development. This review article explores the substantial role of cysteine protease B (CPB) in medicinal chemistry from 2001 to 2024, particularly concerning combatting Leishmania parasites. We delve into contemporary advancements and potential prospects associated with targeting cysteine proteases for therapeutic interventions against leishmaniasis, emphasizing drug discovery in this context. Computational analysis using the pkCSM tool assessed the physicochemical properties of compounds, providing valuable insights into their molecular characteristics and drug-like potential, enriching our understanding of the pharmacological profiles, and aiding rational inhibitor design. Our investigation highlights that while nonpeptidic compounds constitute the majority (69.2%, 36 compounds) of the dataset, peptidomimetic-based derivatives (30.8%, 16 compounds) also hold promise in medicinal chemistry. Evaluating the most promising compounds based on dissociation constant (Ki) and half maximal inhibitory concentration (IC50) values revealed notable potency, with 41.7% and 80.0% of nonpeptidic compounds exhibiting values < 1 µM, respectively. On the other hand, all peptidic compounds evaluated for Ki (43.8%) and IC50 (31.3%) obtained values < 1 µM, respectively. Further analysis identified specific compounds within both categories (nonpeptidic: 1, 2, and 4; peptidic: 48-52) as particularly promising, warranting deeper investigation into their structure-activity relationships. These findings underscore the diverse landscape of inhibitors in medicinal chemistry and highlight the potential of both nonpeptidic and peptide-based compounds as valuable assets in therapeutic development against leishmaniasis.
Keywords: Cysteine protease B; drug design, neglected tropical disease; drug development; leishmaniasis; new compounds